2003
DOI: 10.2139/ssrn.432621
|View full text |Cite
|
Sign up to set email alerts
|

The Deterrent Effect of Capital Punishment: Evidence from a 'Judicial Experiment'

Abstract: We use panel data for 50 states during the 1960-2000 period to examine the deterrent effect of capital punishment, using the moratorium as a ''judicial experiment.'' We compare murder rates immediately before and after changes in states' death penalty laws, drawing on cross-state variations in the timing and duration of the moratorium. The regression analysis supplementing the beforeand-after comparisons disentangles the effect of lifting the moratorium on murder from the effect of actual executions on murder.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 35 publications
(16 reference statements)
0
43
1
Order By: Relevance
“…Of the 10 studies published since 2000, 6 examined whether the mere presence (or absence, because of a moratorium or the law being abolished) of the DP was a deterrent to homicide by entering a binary dummy variable into the regression model that took on the value of 1 if the DP was legal in the state and 0 otherwise (Dezhbakhsh et al, 2003;Dezhbakhsh and Shepherd, 2006;Donohue and Wolfers, 2005;Ekelund, Jackson, Ressler, and Tollison, 2006;Mocan and Gittings, 2003;Zimmerman, 2006). 4 The dummy variable approach implicitly assumes that the deterrent effects of the DP are unrelated to the probability of execution; rather, the mere existence of capital punishment is assumed to exert a deterrent effect that is not systematically stronger in years with higher actual probabilities of execution.…”
Section: Presence Of the Death Penaltymentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 10 studies published since 2000, 6 examined whether the mere presence (or absence, because of a moratorium or the law being abolished) of the DP was a deterrent to homicide by entering a binary dummy variable into the regression model that took on the value of 1 if the DP was legal in the state and 0 otherwise (Dezhbakhsh et al, 2003;Dezhbakhsh and Shepherd, 2006;Donohue and Wolfers, 2005;Ekelund, Jackson, Ressler, and Tollison, 2006;Mocan and Gittings, 2003;Zimmerman, 2006). 4 The dummy variable approach implicitly assumes that the deterrent effects of the DP are unrelated to the probability of execution; rather, the mere existence of capital punishment is assumed to exert a deterrent effect that is not systematically stronger in years with higher actual probabilities of execution.…”
Section: Presence Of the Death Penaltymentioning
confidence: 99%
“…Specifically, Mocan and Gittings (2003) reported that the presence of the DP reduced the annual number of homicides by 64, whereas Zimmerman (2006) concluded that deterrent effects attributed to the presence of the DP were similar for all five methods of execution. The most notable study to use the dummy variable approach, conducted by Dezhbakhsh and Shepherd (2006), treated the U.S. Supreme Court's 1972 decision imposing a moratorium on the DP as a "judicial experiment" by coding states a 1 for each year in which the moratorium was in effect and 0 otherwise. In all specifications (see their Table 8), the coefficient on the DP dummy variable was significant and positive, which indicates that stopping executions increased the homicide rate or that reinstating the DP reduced the homicide rate.…”
Section: Presence Of the Death Penaltymentioning
confidence: 99%
See 1 more Smart Citation
“…We measure the deterrence effects of EC merger policy by employing the methodology from the economics of crime literature spawned by Becker (1968)-see Ehrlich (1972), Polinsky (1980), Shepherd (2004), and Dezhbakhsh and Shepherd (2006) for other studies in this tradition. In this framework, enforcement actions make criminals update their probabilities of being caught and their estimations of the punishments attached with being caught.…”
Section: A Deterrence Frameworkmentioning
confidence: 99%
“…11. In addition, numerous papers have looked at the impact of different sentencing policies on crime rates, like the death penalty, Three Strikes Laws, and Truth-in-Sentencing Laws (Dezhbakhsh and Shepherd 2006;Ehrlich 1975Ehrlich , 1977Helland and Tabarrok 2007;Iyengar 2008;Mocan and Gittings 2003;Ross 2012;Shepherd 2002). Benson, Rasmussen, and Kim (1998) provide empirical support for the claim that it is not simply the aggregate level of police resources that matters, but rather the relative allocation of police resources toward enforcement of particular types of crime.…”
Section: Police Resourcesmentioning
confidence: 99%